2016
DOI: 10.1007/s00203-016-1322-5
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterisation of synthetic operons for biohydrogen technology

Abstract: Biohydrogen is produced by a number of microbial systems and the commonly used host bacterium Escherichia coli naturally produces hydrogen under fermentation conditions. One approach to engineering additional hydrogen production pathways is to introduce non-native hydrogenases into E. coli. An attractive candidate is the soluble [NiFe]-hydrogenase from Ralstonia eutropha, which has been shown to link NADH/NAD+ biochemistry directly to hydrogen metabolism, an activity that E. coli does not perform. In this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…This observation suggested that overexpression of the hybO gene encoding the small subunit alone could be a useful strategy. To test this hypothesis, an E. coli mutant strain was chosen (IC011, Supplementary Table S1), which lacked the genes for the Hyd-1 and Hyd-3 large subunits and also carried in-frame, nonpolar deletions of hybO and hybA [ 20 ]. Although still encoding the Hyd-2 large subunit HybC, this strain has no hydrogenase activity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This observation suggested that overexpression of the hybO gene encoding the small subunit alone could be a useful strategy. To test this hypothesis, an E. coli mutant strain was chosen (IC011, Supplementary Table S1), which lacked the genes for the Hyd-1 and Hyd-3 large subunits and also carried in-frame, nonpolar deletions of hybO and hybA [ 20 ]. Although still encoding the Hyd-2 large subunit HybC, this strain has no hydrogenase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Not only is the hyb operon repressed by IscR [ 15 ], but removal of the iscR gene also has proved beneficial for overproduction of Fe–S cluster-containing proteins [ 38 ]. A version of the IC011 strain carrying a Δ iscR allele (HJ001) [ 20 ] was transformed with pO N or pO C . Once more, the inclusion of an N-terminal His-tag appeared detrimental to protein stability and enzyme assembly, whereas the strain producing HybO with a C-terminal His-tag generated active Hyd-2 in excess of that observed for the native enzyme ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations